PCR-based embryo sex-determination assay in cattle based on the amelogenin gene - Mengistie, Dejenie; Kelbessa, Shelema; Seyoum, Betelhem; Arega, Bezina; Ali, Sayid; Dire, Mosisa; Girmay, Gebrerufael; Bedassa, Abdi; Tegegne, Desiye Tesfaye (Universitas Airlangga, 2025)
The amelogenin gene-based polymerase chain reaction (PCR) assay offers a precise, efficient, and cost-effective approach for embryo sex determination in cattle. This method capitalizes on genetic differences between the X and Y chromosome-linked amelogenin genes, enabling early sex identification critical for livestock management. Our study outlines the methodology, from embryo collection and DNA extraction to PCR amplification and gel electrophoresis analysis. Results consistently demonstrated the assay's reliability, identifies that all examined embryos were female embryos (X/X) across developmental stages with a male and female control (X/Y) (X/X) respectively, validating the technique. This study underscores the assay’s potential for advancing selective breeding and enhancing productivity in the cattle industry.